Exploring the Link between Self-Efficacy and Subjective Well-Being among Students: Mengeksplorasi Hubungan antara Efikasi Diri dan Kesejahteraan Subjektif di Kalangan Mahasiswa - Aggitama, Wahyu Arega; Ansyah, Eko Hardi (Wadah Inovasi Indonesia, 2024)
This study investigates the relationship between self-efficacy and subjective well-being among high school students aged 14 to 19, a crucial developmental phase. Using a quantitative approach with a sample of 133 students selected via simple random sampling from a population of 200, two measurement tools were employed to assess self-efficacy and subjective well-being. Results revealed a strong positive correlation (r = 0.726, p < 0.001) between self-efficacy and subjective well-being, supporting the hypothesis. This finding underscores the significance of self-efficacy in shaping adolescents' emotional and cognitive evaluations of their experiences, suggesting implications for educational and psychological interventions aimed at enhancing student well-being.